Local acts : community-based performance in the United States - Cohen-Cruz, Jan, 1950- (Rutgers series on the public life of the arts., 2005)
The author surveys community-based performance in the US from its roots to present-day popular culture. She describes performances and processes, and shows how ritualism reinforces community identification while aestheticism enables locals to transgress cultural norms.